Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan. (11th October 2022) - Hussain, Azfar; Cao, Jianhua; Ali, Shaukat; Ullah, Waheed; Muhammad, Sher; Hussain, Ishtiaq; Abbas, Haider; Hamal, Kalpana; Sharma, Shankar; Akhtar, Mobeen; Wu, Xiuqin; Zhou, Jinxing
Abstract: Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from 8 to 32 months ( 0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from 16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties. Abstract : During 1960–2016, the ISMI displayed the most coherences compared to the large‐scale CIs over various regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III. The significant coherences in R‐II ranged from 8 to 32 months ( 0.8–2.8 years) through the entire period, whereas the remaining CIs have an almost similar pattern of interannual coherences over various regions. However, IOD and NAO had major coherences compared to the remaining large‐scale CIs ranging from 16 to 64 months (1.3–5.3 years). The AO had the most significant coherences observed in R‐II, III, and VI throughout the study on the decadal/interdecadal scale from 128 months and above (almost 10–15 years).